AB0519 PULMONARY INVOLVEMENT IN ANCA ASSOCIATED VASCULITIS (AAV) ACCORDING TO ANTIGENIC SPECIFICITY: A RETROSPECTIVE ARGENTINE COHORT. (2nd June 2020) - Pena, C.; Savy, F.; Costi, A. C.; Garcia, L.; García, M.
Abstract : Background: The lung in ANCA associated vasculitis (AAV) is one of the most frequently compromised organs (20-80%). The clinical features of pulmonary involvement vary according to the type of vasculitis and some studies have shown its association with the ANCa subtype or antigenic specifity (MPO-ANCA), (PR3-ANCA). Objectives: A-Describe the clinical features and tomographic findings of pulmonary involvement in vasculitis associated with ANCA and its association according to the ANCA subtypes. B-Evaluate outcome, relapses and associated mortality. Methods: Observational, analytical, retrospective study. Data was collected from the medical records and tomographic image files of patient evaluated in rheumatology department in a tertiary level hospital (2007-2019). Patients diagnosed with AAV, who met criteria for ACR 1990 classification or according to nomenclature of Chapel Hill 2012, with thoracic CT performed and dosage PR3 an MPO antibodies by ELISA technique by a pulmonologist and radiologist. Demographic data, subtype of vasculitis, concomitant organic involvement, disease activity evaluated by Birmingham Vasculitis Activity Score v 3 (BVAS v3), time of evolution of pulmonary involvement, ERS – PCR, serum creatinine, ANCA determined by ELISA were collected. The following findings in parenchyma were evaluated by thorax CT: Consolidation, Ground glass opacities, Reticulation, Honeycomb, cavitated or not nodules, Central airway compromise (thickening or stenosis), Bronchiectasis, Peribronchial thickening, Pleural effusion and the following patterns of disease:NIU (Usual Interstitial Pneumonia), NINE (Unspecified Interstitial Pneumonia), HAD (Diffuse Alveolar Hemorrhage) Results: 66/87 patients were included, 59% female, with a mean age of 51 (14 SD) years. GPA 46.9%, MPA 39.4%, EGPA13.6%, median follow-up time of 36 months (RIC 12-77). According to antigenic specificity: 40.9% PR3 positive, 47.6% MPO positive and ANCA negative 11.5%. 74% of the GPA were positive for PR3, and 58% PAM at MPO. BVAS basal: 17.8 + 7.5 DS. Frequency of organic involvement: 81.8% pulmonar, 77% systemic, 57.6% renal, 43% ENT. 54% of patients with pulmonary involvement was present at the onset of their disease. Conclusion: The frequency of pulmonary involvement in this cohort of patients was 82%, similar to that reported in the literature and was presented at the beginning of the disease in half of the cases. The presence of positive MPO was associated with a higher frequency of usual interstitial pneumonia. References: [1]Sophia Lionaki. Classification of ANCA vasculitides: The role of anti-neutrophil cytoplasmic autoantibody specificity for MPO or PR3 in disease recognition and prognosis. Arthritis Rheum. 2012 October; 64(10): 3452–3462. doi:10.1002/art.34562. [2]Kouichi Hirayama. Pulmonary involvements of anti-neutrophil cytoplasmic autoantibody-associated renal vasculitis in Japan Nephrol Dial Transplant (2015) 0: 1–11 doi: 10.1093/ndt/gfu385 .3-Beatrice Feragalli.The Lung in Systemic Vasculitis: Radiological Patterns and Differential Diagnosis. British Institute of Radiology Disclosure of Interests: None declared